A systematic review of the psychological distance of climate change: Towards the development of an evidence-based construct. (June 2022) - Keller, Anna; Marsh, John E.; Richardson, Beth H.; Ball, Linden J.
Abstract: The construct of psychological distance has gained traction as an explanation of why climate change is difficult to act on; it often feels far removed, with impacts arising in remote locations to other people or in an uncertain future. However, recent studies and narrative reviews have pointed out inconsistencies in the conceptualisation, operationalisation and results regarding the psychological distance of climate change, with research evidently struggling to develop the construct and determine its place in explaining and promoting pro-environmental behaviour. This paper presents a systematic review of the literature aimed at building an evidence base on which to develop research on psychological distance. Following a systematic search of three databases, 73 records with 84 individual studies were identified, which measured or manipulated the concept in relation to climate change. We find that psychological distance in the context of climate change is a dynamic, context-specific, multidimensional construct, with a wide variety of approaches to measurement and manipulation. Current theorising (primarily Construal Level Theory) is insufficient in describing the diversity and complexity of distance in the climate-change context. Based on the reviewed studies, we give recommendations for the measurement and manipulation of the construct. However, our overarching suggestion is to focus on specific contexts in which distance plays a role in climate-change cognition and action, such as the perception of impacts, policy or behaviour. We discuss how describing distance within these contexts can help researchers to understand current findings, to disentangle different components of distance beliefs and to incorporate theory and insights from related perspectives. Highlights: Psychological distance is often seen as barrier to climate change action. Evidence so far is inconsistent, both in methodology and findings. Conducted systematic review of 84 studies to build basis for construct development. Suggest focusing on specific contexts within climate change to develop field. Separating different distance components may further reduce inconsistencies.